Sensory profiles and hexanal content of cracker-coated and roasted peanuts stored under different temperatures - Grosso, Nelson (2008)
Mean values of oxidized and cardboard flavor intensities and hexanal content increased significantly in cracker-coated peanut (CCP) and roasted peanut (RP) samples stored at 23, 30 and 40C, while intensity of roasted peanutty flavor decreased during storage. Prediction models for these sensory attributes from time and temperature variables were developed. Hexanal content could not be predicted from storage time and temperature of CCP and RP. Flushing RP with nitrogen had a protective effect against development of oxidized flavors, not observed in CCP. The coating of CCP contributed to the development of oxidized flavor. When oxidized flavor (= 36.2) was used as an indicator of storage deterioration, CCP had a predicted shelf life of 78, 56 and 32 days at 23, 30 and 40C, respectively, whereas in RP it was 116, 105 and 94 days, respectively. Sensory profiles predicted shelf life of RP and CCP better than hexanal content.